2015
DOI: 10.1038/ncomms7527
|View full text |Cite
|
Sign up to set email alerts
|

Onset of sediment transport is a continuous transition driven by fluid shear and granular creep

Abstract: Fluid-sheared granular transport sculpts landscapes and undermines infrastructure, yet predicting the onset of sediment transport remains notoriously unreliable. For almost a century, this onset has been treated as a discontinuous transition at which hydrodynamic forces overcome gravity-loaded grain–grain friction. Using a custom laminar-shear flume to image slow granular dynamics deep into the bed, here we find that the onset is instead a continuous transition from creeping to granular flow. This transition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
206
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(227 citation statements)
references
References 36 publications
20
206
0
Order By: Relevance
“…Our findings are consistent with observed segregation phenomena in bidisperse beds known as riverbed armoring: a slow process in which the bed segregates in a top region with large particles and a region below with smaller particles [5,19]. Recently, it has been found that such granular creep is very similar to kinetic sieving processes in dry granular flows [14].…”
Section: Bidisperse Bedsupporting
confidence: 91%
“…Our findings are consistent with observed segregation phenomena in bidisperse beds known as riverbed armoring: a slow process in which the bed segregates in a top region with large particles and a region below with smaller particles [5,19]. Recently, it has been found that such granular creep is very similar to kinetic sieving processes in dry granular flows [14].…”
Section: Bidisperse Bedsupporting
confidence: 91%
“…Furthermore, when such techniques can be used simultaneously for rheological characterization, they provide crucial insights into the coupling between particle dynamics and the macroscopic flow behavior of the suspension. For transparent suspending fluids and large enough particles, as in the case of geophysical flows, direct particle tracking is possible [7]. However, suspensions of smaller particles are generally opaque for volume fractions above a few percent, so the optical investigation of denser systems generally involves more advanced techniques such as confocal scanning light microscopy [8,9] or depolarized light scattering [10].…”
Section: Introductionmentioning
confidence: 99%
“…While the role of turbulence has received the most attention, granular contributions to bed-load dynamics are increasingly being recognized (Frey and Church (2011a); Houssais et al (2015); Maurin et al (2016)). One of the defining features of granular systems is a continuous transition from flowing to static 5 regimes known as the jamming transition.…”
mentioning
confidence: 99%
“…Experiments show that the onset of bed-load transport has the hallmarks of a jamming transition (Houssais et al (2015); Maurin et al (2016); Houssais et al (2016)). Near-threshold transport rates exhibit strong correlations and intermittency, while fluxes at rates far above threshold are uncorrelated and smooth (Singh et al (2009)).…”
mentioning
confidence: 99%
See 1 more Smart Citation